2011
DOI: 10.1024/1662-9647/a000037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a TEACCH- and Music Therapy-Based Psychological Intervention in Mild to Moderate Dementia

Abstract: Background: A multicomponent psychological intervention designed to alleviate neuropsychiatric symptoms and to improve communication in mild to moderate dementia was evaluated in a controlled trial. Components were (1) TEACCH (Treatment and Education of Autistic and related Communication handicapped Children)-based cognitive-behavioral and environmental interventions adapted for dementia and (2) music therapy. Methods: In a Pre-post design, the treatment group (n = 26) received the program for 6 months, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 16 publications
0
26
0
3
Order By: Relevance
“…improved emotional and behavioral functioning in the same way [65,67,69] . Characteristics of the studies and main results have been summarized in Table 1.…”
Section: Researchmentioning
confidence: 61%
See 3 more Smart Citations
“…improved emotional and behavioral functioning in the same way [65,67,69] . Characteristics of the studies and main results have been summarized in Table 1.…”
Section: Researchmentioning
confidence: 61%
“…Two studies revealed no significant effect of musical intervention [64,66] while in three studies both experimental and control group Choi et al [61] CCT (1) Positive trends for GDS and GQoL in music group. Improvements in BPDS (P = 0.004) and caregiver distress (P = 0.003) Guètin et al [62] RCT (3) [63] RCT (3) Cooke et al [64] RCT (3) [65] CCT (0) [66] RCT ( No effects on mood. Improvements (P < 0.05) for MPI, MPD, attentional matrices, ADL, SVAM, and GMP Janata [67] RCT (3) [68] RCT (2) [69] RCT (2) Chu et al [70] RCT ( Raglio A et al .…”
Section: Effects On Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…) and four quasi‐experimental studies (van Weert et al . , Tappen & Williams , Fischer‐Terworth & Probst , Hattori et al . ).…”
Section: Resultsmentioning
confidence: 99%